Diversity Analysis in Finger Millet (Eleusine coracana L.) Germplasm for Agro-Morphological and Grain Yield Attributing Traits - Elangovan, Maruthamuthu; Venkatesh, Karnam; Annapurna, A; Patil, Rajendragouda; Kiran, Ravi; Pandey, Sushil; Pandey, Chitra Devi (Journal of Cereal Research, 2022)
Finger millet (Eleusine coracana L.) is an important millet crop grown at large scale in Asia and Africa. Germplasm is the basic source of variation in the crop improvement. An experiment on characterization of 2000 germplasm accessions was conducted in augmented design at ICAR-Indian Institute of Millets Research (IIMR), Hyderabad during Kharif 2017. The multivariate analysis is an important statistical tool which can easily asses the polygenic traits important for breeding program. The PCA analysis showed 14 Principle Components (PCs) to total variability. The first six principal components explained a total of 63.99% of variability with Egan’s value of >1. The first two PCs played important role in diversity contribution than other PCs. A total of nine clusters were formed on the bases of Euclidian distance of 14.67% and 85, 63% variation observed within and between clusters. The selection of genotypes from the different clusters will help the breeders to increase variability in their breeding programme.